2024
DOI: 10.3390/pharmaceutics16030421
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Mucoadhesive Oral Care Gel Containing Kaempferia galanga Extract

Indah Suasani Wahyuni,
Irna Sufiawati,
Amira Shafuria
et al.

Abstract: The rhizome of Kaempferia galanga (Zingiberaceae) is extensively used in traditional medicine by utilizing its various biological activities. It has been proven that ethyl-para-methoxycinnamate (EPMC) and other polyphenolic compounds are present in considerable amounts in the ethanolic extract of K. galanga rhizome (EKG). Our previous study confirmed that a dose of 0.5–1% of EKG demonstrated anti-inflammatory activity and a wound-healing effect in chemical-induced oral mucosal ulcers of Wistar rats. Currently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…Recent studies have shown that different extracts from Kaemfpferia galangal Linn. present activities such as anti-angiogenic, anti-inflammatory, and antiviral [6][7][8]. Key components found in the rhizome extract of Kaempferia galanga include cinnamic acid derivatives such as ethyl p-methoxycinnamate (EPMC) and ethyl cinnamate, as well as flavonoids such as kaempferol, known for their antioxidant, antimicrobial, and anti-cancer properties [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that different extracts from Kaemfpferia galangal Linn. present activities such as anti-angiogenic, anti-inflammatory, and antiviral [6][7][8]. Key components found in the rhizome extract of Kaempferia galanga include cinnamic acid derivatives such as ethyl p-methoxycinnamate (EPMC) and ethyl cinnamate, as well as flavonoids such as kaempferol, known for their antioxidant, antimicrobial, and anti-cancer properties [9].…”
Section: Introductionmentioning
confidence: 99%